Doses de extrato de própolis na nutrição e crescimento vegetativo de feijoeiro - Nakagawa, Eduardo Seiki (2014)
There is little information about the effects of the ethanolic extract of propolis (EEP) was studied in common bean. The aim of this study was to investigate the effects of foliar application of ethanol extract of propolis (EEP) on vegetative growth. The water loss and productivity cv. Valente bean. The experiment was conduct at Dona Isabina, farm, from February to May 2012. The experimental design was used on randomized block, five repetition, using cultivate Valente the treatments were as five concentrations of EEP (0; 212; 424; 636; and 848 g ha-1),and the extract made with 10% crude propolis (propolis originating from the coast of Paraná) and 90% alcohol 96ºGL . only for variables, chlorophyll content and stem diameter we used layout in split plot. The application of EEP at the concentration of 1,2% of EEP maintained higher 16,22% above control which was 62,36%, attributing this effect to the accumulation of was present in propolis on leaf surface. The EEP also increased the levels of Mg and chlorophyll in the leaves, increasing the content of chlorophyll in leaves and vegetative growth, which served the increase as energetic increase, increasing the productivity on the Cv.Valente bean bag at 8,08 sc ha-1or 485 kg ha-1.